Influence of High Latitude Sudden Stratospheric Warming on Tropical Weather: Observations From a 205 MHz Stratosphere Troposphere Radar and Surface Meteorological Parameters. Issue 4 (27th April 2021) - Remya, R.; Manoj, M. G.; Rakesh, V.; Mohanakumar, K.; Sivan, C.
Abstract: The study illustrates the evidence of dynamical coupling between the high‐latitude sudden stratospheric warming (SSW) events that occurred in three consecutive winter seasons and the concomitant changes in the wind pattern in the lower stratosphere and troposphere observed with a state‐of‐the‐art 205 MHz stratosphere‐troposphere wind profiling Radar, located at Cochin (10.03°N, 77.33°E), a tropical station in southwest peninsular India. Associated with the occurrence of SSW, the tropical region experiences a change in zonal wind speed and direction at upper tropospheric altitudes after the central day of warming. The zonal wind in the troposphere also reversed its prevailing direction. Downward propagation of zonal wind during the SSW period is noticed, which is also supported by the reanalysis data set. In the lower troposphere, vertical wind experienced sudden fluctuations with varying amplitudes soon after the peak day of the SSW event. The surface meteorological parameters in an area (8°–12°N, 74°–78°E), centered at Cochin, from ERA‐Interim are also examined. An abrupt fall in outgoing longwave radiation, followed by convection and unusual rainfall in the tropical region 5–6 days before the peak of SSW events, is a unique and exciting feature noted in the study. Detailed analysis of the past 20 years of SSW events confirmed the observational evidence of unusual rainfall over the low latitude region related with the onset of SSW. Comprehensive observational and numeric modeling studies are needed to understand the mechanism for the SSW events in high latitudes and the associated convective activity and precipitation in the low latitude region. Key Points: Wind profiling Radar observation of impact of stratospheric warming (SSW) over tropics Upper tropospheric zonal wind decreased or reversed its prevailing direction and Downward propagation of zonal winds during the SSW Vertical wind experienced sudden fluctuations and an abrupt fall in OLR, followed by convection and unusual rainfall in the tropical region